Narrative Inquiry: The Success Story of An Autodidact Entrepreneur - Saefudin, Akhmad; Basit, Abdul (School of Business, IPB University (SB-IPB), 2024)
Background: Entrepreneurial activities have a significant role in encouraging poverty alleviation, increasing prosperity, and creating job opportunities. Thus, it is urgent to publish the stories of successful entrepreneurs to spur the growth of new/young/budding ones.Purpose: This research aims to reveal the successful business journey of Buntoro (68 years), a self-taught entrepreneur who started his business from scratch.Design/methodology/approach: This research describes the success of an entrepreneur who dropped out of fifth grade elementary school using a narrative approach. Findings/Result: Buntoro’s success story has similarities and differences with Antony Boaging –a businessman from the Philippines who is famous for Boaging’s Bread. But, in some ways Buntoro could be said to be superior and more inspiring.Conclusion: An entrepreneur must have an entrepreneurial mind-set: highly motivated to succeed, resilient (tough), innovative and adaptive to changing situations.Originality/value (State of the art): Buntoro is a sort of entrepreneur who thinks globally and acts locally. He success is rooted in his hometown, then spread out of the region. Keywords: entrepreneurship, self-taught, hard work, business journey, autodidact entrepreneur